2019
DOI: 10.3390/genes10090679
|View full text |Cite
|
Sign up to set email alerts
|

The Duplicated Y-specific amhy Gene Is Conserved and Linked to Maleness in Silversides of the Genus Odontesthes

Abstract: Sex-determining genes have been successively isolated in several teleosts. In Odontesthes hatcheri and O. bonariensis, the amhy gene has been identified as a master sex-determining gene. However, whether this gene is conserved along related species is still unknown. In this study, the presence of amhy and its association with phenotypic sex was analyzed in 10 species of Odontesthes genus. The primer sets from O. hatcheri that amplify both amhs successfully generated fragments that correspond to amha and amhy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 31 publications
1
25
0
1
Order By: Relevance
“…In another Oryzias species, the sex-determinant is a Y-specific copy of the gsdf gene [ 15 ]. The sex-determining gene in the Patagonian pejerrey Odontesthes hatcheri is a duplication of the anti-Müllerian hormone amh [ 16 , 17 ]. Amh has also been duplicated to become the sex-determining gene in the Northern pike Esox lucius [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another Oryzias species, the sex-determinant is a Y-specific copy of the gsdf gene [ 15 ]. The sex-determining gene in the Patagonian pejerrey Odontesthes hatcheri is a duplication of the anti-Müllerian hormone amh [ 16 , 17 ]. Amh has also been duplicated to become the sex-determining gene in the Northern pike Esox lucius [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have reported a discordance between phenotypic and sdY sex within the Salmonidae family ( Eisbrenner et al, 2014 ; Cavileer et al, 2015 ; Larson et al, 2016 ; Podlesnykh et al, 2017 ). Discordance between DNA markers for sex and phenotypic sex is not uncommon in fishes, and it is typical in a species displaying a combination of genetic and environmental sex determination ( Hattori et al, 2019 ). However, environmental sex determination has not been reported in the family Salmonidae, and several alternative theories for this discordance have been put forward including phenotyping errors ( Yano et al, 2013 ; Eysturskarð et al, 2017 ), sex reversal ( Nagler et al, 2001 ; Williamson and May, 2002 ; Metcalf and Gemmell, 2006 ), loss of gene function ( Podlesnykh et al, 2017 ), or dose effects ( Brown et al, 2020 ) among others ( Guyomard et al, 2014 ; Larson et al, 2016 ; King and Stevens, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The target of this study was the cobaltcap silverside Hypoatherina tsurugae, a marine atherinid with broad distribution and ecological importance as a forage species in coastal environments of Japan and South Korea (Mori, Kimura, Tsukamoto, Kawano, & Yoshida, 1988). In this species, we recently demonstrated the existence of a homologue of the male sex determining gene amhy of other atheriniforms (Y chromosome-linked anti-Müllerian hormone; Hattori et al, 2012Hattori et al, , 2019Yamamoto et al, 2014) and its close association with phenotypic sex in animals born and reared in captivity at a constant temperature equivalent to the mean temperature during the spawning season (Bej et al, 2017). The primary objective of this study was to clarify if this GSD can be overturned by high and low temperatures during gonadal sex differentiation.…”
mentioning
confidence: 99%